"Modest doubt is called the beacon of the wise"—Incorporating uncertainty in risk analysis from Shakespeare to today. Issue 5 (3rd April 2023) - Wu, Felicia; Trump, Benjamin D.
Abstract: "Modest doubt is call'd the beacon of the wise."—William Shakespeare, Troilus and Cressida . Although the character Hector warns his fellow Trojans with this line not to engage in war against the Greeks, Shakespeare's works are replete with characters who do not incorporate modest doubt, or any consideration of uncertainty, in their risk decisions. Perhaps Shakespeare was simply a keen observer of human nature. Although risk science has developed tremendously over the last five decades (and scientific inquiry over five centuries), the human mind still frequently defaults to conviction about certain beliefs, absent sufficient scientific evidence—which has effects not just on individual lives, but on policy decisions that affect many. This perspective provides background on the Shakespearean quote in its literary and historical context. Then, as this quote is the theme of the 2023 Society for Risk Analysis Annual Meeting, we describe how "modest doubt"—incorporating the notion of uncertainty into risk analysis for individual and policy decisions—is still the "beacon of the wise" today.